2018
DOI: 10.48550/arxiv.1805.11627
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scalar Correlators in Bosonic Chern-Simons Vector Models

Abstract: We consider the planar limit of Chern-Simons theories coupled to a scalar φ in the fundamental representation of a U (N ) k gauge group, at both the regular and Wilson-Fisher conformal points. These theories have one single-trace scalar operator J 0 = φφ. We calculate its connected planar n-point functions, when all the external momenta are collinear. More specifically, we derive an algebraic recurrence relation that expresses each such n-point function in terms of lower-point ones. As an application, we study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…In order to evaluate the results, we utilize two interesting techniques. The first technique involves inversion of all the momenta appearing in the integral (See appendix.A.1 and section 5.3.2 of [36] and [37]). Through this method one may compute three dimensional box integrals in momentum space easily and efficiently.…”
Section: Four Point Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to evaluate the results, we utilize two interesting techniques. The first technique involves inversion of all the momenta appearing in the integral (See appendix.A.1 and section 5.3.2 of [36] and [37]). Through this method one may compute three dimensional box integrals in momentum space easily and efficiently.…”
Section: Four Point Functionsmentioning
confidence: 99%
“…For the box scalar integration (A.4), we have used inversion technique used in [36,37]. This technique involves inverting all the momenta including the integration variable as follows l µ = lµ l2 and p i = Pi P 2 (i = 1, 2, 3).…”
Section: A Compendium Of Integralsmentioning
confidence: 99%
“…n,s . At order 1/N it is not known how to directly compute the four-point function of the CS theories by field theory methods, though it is known in some specific kinematic regimes [7,14,15]. However, one can determine the correlation function almost uniquely just from bootstrap considerations.…”
Section: Introductionmentioning
confidence: 99%
“…Here we will determine the same for the quasi-bosonic theory. The four point function of the scalar operator has been studied in a specific kinematic and parameter regime in [55,59]. Recently, it was demonstrated that in the large-N limit, this correlation function in position space is determined by the free theory answer upto a conformal partial wave which is given by a certain D function as follows [89]…”
Section: Four Point Functionmentioning
confidence: 99%